Aerobic fitness and the sleeping brain of adolescents—a pilot study. Issue 1 (9th April 2021) - Neikrug, Ariel B; Mander, Bryce A; Radom-Aizik, Shlomit; Chen, Ivy Y; Stehli, Annamarie; Lui, Kitty K; Chappel-Farley, Miranda G; Dave, Abhishek; Benca, Ruth M
Abstract: Study Objectives: Aerobic fitness (AF) and sleep are major determinants of health in adolescents and impact neurocognitive and psychological development. However, little is known about the interactions between AF and sleep during the developmental transition experienced across adolescence. This study aimed to consider the relationships between AF and habitual sleep patterns and sleep neurophysiology in healthy adolescents. Methods: Subjects (mean age = 14.6 ± 2.3 years old, range 11–17, 11 females) were evaluated for AF (peak VO2 assessed by ramp-type progressive cycle ergometry in the laboratory), habitual sleep duration and efficiency (7–14 days actigraphy), and topographic patterns of spectral power in slow wave, theta, and sleep spindle frequencies in non-rapid eye movement (NREM) sleep using overnight polysomnography (PSG) with high-density electroencephalography (hdEEG, 128 channels). Results: Significant relationships were observed between peak VO2 and habitual bedtime ( r = −0.650, p = .009) and wake-up time ( r = −0.603, p = .017), with greater fitness associated with going to bed and waking up earlier. Peak VO2 significantly predicted slow oscillations (0.5–1 Hz, p = .018) and theta activity (4.5–7.5 Hz, p = .002) over anterior frontal and central derivations ( p < .001 and p = .001, respectively) after adjusting for sex and pubertal development stage. Similar associations were detected for fast sleep spindle activity (13–16 Hz, p = .006), which was greater over temporo-parietal derivations. Conclusions: Greater AF was associated with a more mature pattern of topographically-specific features of sleep EEG known to support neuroplasticity and cognitive processes and which are dependent on prefrontal cortex and hippocampal function in adolescents and adults. AF was also correlated with a smaller behavioral sleep phase delay commonly seen during adolescence.